Training and individual performance in Europe - Pfeiffer, Friedhelm (ZEW, 2000)
Learning at school and university and also at the work place has become more important in the knowledge-based economy. This paper provides a critical review of recent econometric work on the determinants and impacts of training in Europe. Training has non negligible positive effects for firms and trainees; for the group of non trainees potential negative effects has been found in some studies. The incidence and the impact of training depend on the national education and training system. However, selectivity, individual heterogeneity, self selection, diversity of training institutions and general equilibrium effects seem to play an important role in all training systems.
Literaturverz. S. 30 - 34
Keywords: Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Bildungswesen; Berufsbildung; Bildungsinvestition; Bildungsertrag; Mikroökonometrie; Schätzung; Bildungsverhalten; EU-Staaten